Electric field structures and waves at plasma boundaries in the inner magnetosphere. Issue 6 (2nd June 2015) - Malaspina, David M.; Wygant, John R.; Ergun, Robert E.; Reeves, Geoff D.; Skoug, Ruth M.; Larsen, Brian A.
Abstract Recent observations by the Van Allen Probes spacecraft have demonstrated that a variety of electric field structures and nonlinear waves frequently occur in the inner terrestrial magnetosphere, including phase space holes, kinetic field line resonances, nonlinear whistler mode waves, and several types of double layer. However, it is unclear whether such structures and waves have a significant impact on the dynamics of the inner magnetosphere, including the radiation belts and ring current. To make progress toward quantifying their importance, this study statistically evaluates the correlation of such structures and waves with plasma boundaries. A strong correlation is found. These statistical results, combined with observations of electric field activity at propagating plasma boundaries, are consistent with the scenario that the sources of the free energy for the structures and waves of interest are localized near and comove with these boundaries. Therefore, the ability of these structures and waves to influence plasma in the inner magnetosphere is governed in part by the spatial extent and dynamics of macroscopic plasma boundaries in that region.